Author Correction: CDCP1 expression is frequently increased in aggressive urothelial carcinoma and promotes urothelial tumor progression (Scientific Reports, (2023), 13, 1, (73), 10.1038/s41598-022-26579-z) - Saponaro, Miriam; Flottmann, Sina; Eckstein, Markus; Hommerding, Oliver; Klümper, Niklas; Corvino, Dillon; Hosni, Sana; Schmidt, Anja; Mönig, Nicolas; Schmidt, Doris; Ellinger, Jörg; Toma, Marieta; et al. (Scientific Reports, 2023)
Tables 1 and 2 in the original version of this Article presented redundant for the research information. To increase their readability, data in both Tables was summarized. The original Article has been corrected.
CRIS-Team Scopus Importer:2023-03-03